Can MRI Observations Predict Treatment Outcome of Lavage in Patients with Painful TMJ Disc Displacement without Reduction? - EwaCarin Ekberg; Lars-Göran Hansson; Thomas List; Lars Eriksson; Lotta Englesson Sahlström; Arne Petersson (Stilus Optimus, 2015)
Objectives: The purpose of this study was to examine magnetic resonance imaging findings in patients with painful disc displacement without reduction of the temporomandibular joint to determine whether the findings were able to predict treatment outcome of lavage and a control group treated with local anaesthesia without lavage in a short-term: 3-month perspective. Material and Methods: Bilateral magnetic resonance images were taken of 37 patients with the clinical diagnosis of painful disc displacement without reduction. Twenty-three patients received unilateral extra-articular local anaesthetics and 14 unilateral lavage and extra-articular local anaesthetics. The primary treatment outcome defining success was reduction in pain intensity of at least 30% during jaw movement at the 3-month follow-up. Results: Bilateral disc displacement was found in 30 patients. In 31 patients the disc on the treated side was deformed, and bilaterally in 19 patients. Osteoarthritis was observed in 28 patients, and 13 patients had bilateral changes. Thirty patients responded to treatment and 7 did not, with no difference between the two treated groups. In neither the treated nor the contralateral temporomandibular joint did treatment outcome depend on disc diagnosis, disc shape, joint effusion, or osseous diagnoses. Magnetic resonance imaging findings of disc position, disc shape, joint effusion or osseous diagnosis on the treated or contralateral side did not give information of treatment outcome. Conclusions: Magnetic resonance imaging findings could not predict treatment outcome in patients treated with either local anaesthetics or local anaesthetics and lavage.